Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Pada Pembelajaran Olahraga Mahasiswa PGSD di STAHN Mpu Kuturan Singaraja - Gusti Ngurah Arya Yudaparmita; Komang Surya Adnyana (STAHN Mpu Kuturan Singaraja, 2022)
Education plays an important and strategic role in producing quality Human Resources (HR) who will build the nation. Education must be able to accommodate and provide solutions in an effort to advance and win the tough and tight global competition, if it wants to survive productively in the midst of global competition. Through physical education provided with the CTL model, it is hoped that students can gain various experiences to express personal impressions that are fun, creative, innovative, skilled, improve and maintain physical fitness and understanding of human movement.